Aristotle and Husayn Waiz Kashifi: Harmony in Moral Views (Texas Journal of Philology, Culture and History, 2022)
In this country, the influence of the ancient Greek mushils is considered, in the private philosophy of morality of Aristotle, based on the principle of rationality, which is a motivating influence on the moral and philosophical teachings of Husayn Waiz Kashifi